Analisis Penerapan Iso 9001:22000 Terhadap Volume Penjualan Lokal : Studi Kasus Di PT. Indo Calli Plast - Galih Oktavian; Erna Indriastiningsih; Agung Widiyanto Fajar Sutrisno; Yunita Primasanti (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
PT Indo Calli Plast experienced a decline in sales in 2015-2023. Therefore, the company is trying to increase product sales by implementing ISO 9001:22000 in 2023 so that it can compete to customer. This research aims to determine the conditions of ISO implementation at PT Indo Calli Plast and to determine the effect of implementing ISO 9001:22000 on local sales volume at PT Indo Calli Plast. This type of research uses qualitative descriptive research. Data collection techniques used questionnaires, observations and interviews at PT Indo Calli Plast. The data processing method in this research uses a semi-qualitative analysis method, namely a combination of qualitative and quantitative research. SPSS Data Processing, including: Validity and Reliability Test, Classic Assumption Test, Hypothesis Test. The results of this research: The implementation of ISO 9001:22000 has a positive and significant effect on the local sales volume of PT Indo Calli Plast. The results of the coefficient of determination test (R2) in the table above, obtained an R Square value of 0.844. This means that 84.4% of the Local Sales Volume at PT Indo Calli Plast is influenced by the ISO 9001:22000 Implementation variable, while the remaining 15.6% is influenced by other variables not explained in this research.